Detection of early motor involvement in diabetic polyneuropathy using a novel MUNE method – MScanFit MUNE. Issue 10 (October 2019) - Kristensen, A.G.; Bostock, H.; Finnerup, N.B.; Andersen, H.; Jensen, T.S.; Gylfadottir, S.; Itani, M.; Krøigård, T.; Sindrup, S.; Tankisi, H.
Highlights: MScanFit MUNE yields detailed information on motor unit loss. Motor involvement in diabetic neuropathy may be present as early as sensory involvement. MScanFit MUNE provides sensitive detection of motor involvement in diabetic polyneuropathy. Abstract: Objective: Detection of motor involvement in diabetic polyneuropathy (DPN) by nerve conduction studies (NCS) does not occur until there is substantial loss of motor units, because collateral reinnervation maintains compound muscle action potential (CMAP) amplitude. Motor unit number estimation (MUNE) methods may therefore be more sensitive. This study was undertaken to test whether the novel method, MScanFit MUNE (MScan) can detect motor involvement in DPN despite normal NCS. Methods: Fifty-two type-2 diabetic patients and 38 healthy controls were included. The median nerve was examined in all participants using standard NCS and a detailed CMAP scan, used for MScan. Additional lower extremity NCS in patients were used for DPN diagnosis. Results: Of 52 diabetic patients, 21 had NCS-defined DPN while lower extremity NCS were normal in 31 patients. MScan motor unit number and size showed higher sensitivity and incidence of abnormality than motor NCS parameters, and a similar sensitivity to sensory NCS. Conclusions: MScan is able to detect motor axonal damage at times when collateral reinnervation limits NCS changes. Significance: MScan is a sensitive method to detect motor involvement in DPN, which our data suggests is present as early as sensory.